Marine chemistry - Wangersky, Peter J. (Peter John) (Handbook of environmental chemistry. Water pollution, 2000)
The carbon dioxide absorption and gas exchange at the sea surface, marine aerosols and their photochemistry, the oceanic carbon cycle as well as biomarkers in marine ecosystems, and related topics are of primary importance for understanding our global ecosystem. The topics addressed in this volume are all stemming from areas which have developed only in the last ten years of research or which have gone into decidedly new directions in that time. In most cases, the recent research has been driven by advances in instrumentation or by large-scale international cooperations. Thus this volume is also aiming at interdisciplinary and international cooperations in the future.